Photoluminescence spectral broadening, chirality transfer and amplification of chiral perovskite materials (R-X-p-mBZA)2PbBr4 (X = H, F, Cl, Br) regulated by van der Waals and halogen atoms interactions. Issue 30 (20th July 2020) - Zhou, Chenyang; Chu, Ya; Ma, Linlin; Zhong, Yingqian; Wang, Chao; Liu, Yalan; Zhang, Haoyue; Wang, Beibei; Feng, Xia; Yu, Xi; Zhang, Xiaotao; Sun, Yan; et al.
Abstract : We introduced halogen-substituted chiral molecules as A-site cations to synthesize a series of novel organic–inorganic hybrid 2D chiral perovskite materials (R-X- p -mBZA)2 PbBr4 (X = H, F, Cl, Br; p : para -position; mBZA = α-methylbenzylamine). Abstract : In this work, we introduced halogen-substituted chiral molecules as A-site cations to synthesize a series of novel organic–inorganic hybrid two-dimensional (2D) chiral perovskite materials (R-X- p -mBZA)2 PbBr4 (X = H, F, Cl, Br; p : para -position; mBZA = α-methylbenzylamine) for the first time. This halogen-substituted cation strategy collectively solved problems of narrow emission, weak chirality and low photoluminescence quantum yield (PLQY) for the emerged chiral perovskites. Photoluminescence (PL) spectra are significantly broadened due to the additional emission from self-trapped excitons (STEs) besides free excitons (FEs) states modulated by introducing significant disorder to the Pb–Br–Pb angle. The chirality of A-site chiral molecules is transferred and amplified to entire perovskite materials by fixing the chiral molecules at A-site via the interaction of halogen atoms. Furthermore, their PLQYs are improved with the reduction of energy gap and inhibition of the non-radiative transition from STEs to ground state. The halogen-substituted A-site cation strategy can be performed to develop organic–inorganic hybrid chiral perovskites with various optoelectronic applications.